Smart Drinking Control System Based on Raspberry Pi - Sung-Bae Kim; Ki-Young Lee; Sung-Ho Hwang; Yeon-Man Jeong; Jeong-Jin Kang (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Currently, police officers randomly arrange sobriety checkpoints and verify drunk drivers on the road through breath test. Regardless of such efforts of police officers, people share and avoid the locations of driving under the influence (DUI) checkpoint cunningly. The purpose of this study is to design and implement a system that prevents drunk drivers from taking their car out and easily connects the drivers to a chauffeur service provider using Arduino, Voyager face recognition camera, and OpenCV. This system enables an efficient allocation of police officers who check drunk driving based on DUI parking lot checkpoints and creates profit by connecting drivers to a chauffeur service provider, resulting in the reduction of drunk driving victims.